RANCANGAN SISTEM INFORMASI PELAYANAN PASIEN PADA PUSKESMAS PANCORAN MAS DEPOK - Santi Widianti (Universitas Amikom Purwokerto, 2010)
In information era at this time all humans in every its life aspect expect a quick and precise service either in good health or pain situation. As well as the things of with expected by each other element of form system in Puskesmas Pancoran Mas. Insufficient patient satisfaction only with nice tidaknya puskesmas, its professional Dokter and medical roof its, but also hung from quick and precisely information service that required patient. By using tool of system design, then developed an information system until facilitate in the case of keep, modification, process and access data in accordance with needed. This system is expected time that used to access data like patient data, medicine, history of patient health can be quicker, efficient and safe in its r epository and accurate. A quality information and good communication network between department will increased productivity of officer.Design of information system if used is opportunity for Puskesmas to improve service and professionalism